Moving toward the Museum: The Collection of Antique Spolia - Shaw, Wendy (Possessors and Possessed, 2003)
In 1996 the Turkish Ministry of Culture hosted ceremonies and a conference commemorating the sesquicentennial of museums in Turkey. Celebrations of the centennial anniversary in 1946 had established their definitive birth year. Nonetheless, in 1996 several interested parties debated the suitability of this date. Although the Ottoman government first sanctioned the collection of antiquities in 1846, some people argued that 1723 was a more appropriate starting date. In that year the Ottoman government remodeled the former Church of Hagia Irene, in use as an artillery warehouse, and included a display of valuables in the renovated structure. Others argued that the